TINGKAT FINANSIAL LITERASI MASYARAKAT KOTA GORONTALO DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Payu, Boby Rantow; Selvi, Selvi (FRONTIERS: JURNAL SAINS DAN TEKNOLOGI, 2018)
Scam investment phenomena raises in Indonesian people in recent years, includes in Gorontalo. This shows that level of understanding and knowledge of the people about financial investment product is still low. Therefore, this research aims to measure to what extent level of financial literacy of people in Gorontalo City. This research was conducted by considering the importance of financial literacy as factors that determines mostly economic growth thus it is an agenda campaigned by Bank of Indonesia and Financial Service Authority (OJK). This research aims to investigate level of financial literacy of Gorontalo City people based on factors of demography, social and economic. In addition, it also aims to obtain applicable model and strategy of approach in terms of improving level of financial literacy of the people. This is a descriptive quantitative research. Then, it applies descriptive and crosstab analysis. Research finding reveals that level of financial literacy of Gorontalo City people is good. For conventional product, it is categorized very good while for non-conventional product, level of financial literacy of people in Gorontalo Province is very low. Therefore, more intense socialization and education are needed by mean of minimizing potency of scam investment.Keywords: financial literacy, investment, financial